Food insecurity and frailty among women with and without HIV in the United States: a cross‐sectional analysis. Issue 6 (14th June 2021) - Tan, Judy Y; Sheira, Lila A; Frongillo, Edward A; Gustafson, Deborah; Sharma, Anjali; Merenstein, Daniel; Cohen, Mardge H; Golub, Elizabeth; Edmonds, Andrew; Ofotokun, Igho; Fischl, Margaret; Konkle‐Parker, Deborah; et al.
Abstract: Introduction: Frailty is frequently observed among people with HIV, and food insecurity is associated with frailty in the general population. Evidence is scarce on the associations between food insecurity and frailty among women with HIV who may be particularly vulnerable to the impacts of food insecurity. The goal of this study was to assess associations between food insecurity and frailty among women with and without HIV. Methods: There were 1265 participants from the Women's Interagency HIV Study who participated in frailty assessments in 2017. Frailty was measured using the Fried Frailty Phenotype, and women were subsequently categorized as robust, pre‐frail or frail. Food insecurity was assessed using the U.S. Household Food Security Survey Module, with women categorized as having high, marginal, low or very low food security. Multinomial logistic regression models were conducted to examine cross‐sectional associations between food insecurity and frailty while adjusting for socio‐demographic, behavioural and HIV status covariates. Results and discussion: Approximately one‐third (31.9%) of the women had marginal, low or very low food security, and the proportions of women who met the criteria for frailty or pre‐frailty were 55.6% and 12.4% respectively. In the adjusted model, the relative risk ratio (RRR) of frailty for women with very low food security versus women with high food security was 3.37 (95% CI [1.38 to 8.24], p  < 0.01); the corresponding RRR of pre‐frailty was 3.63 (95% CI [1.76 to 7.51], p  < 0.001). Higher annual household income was associated with lower RRRs of frailty or pre‐frailty ( p  < 0.01). Similarly, older age was associated with more frequent frailty (RRR=1.06, 95% CI [1.03 to 1.09], p  < 0.001). HIV serostatus was not significantly associated with either pre‐frailty (RRR=0.97, 95% CI [0.71 to 1.31]) or frailty (RRR=0.75, 95% CI [0.48 to 1.16]). Conclusions: Very low food security was associated with more frequent frailty and pre‐frailty among women with and without for HIV. HIV serostatus was not associated with frailty.